2021
DOI: 10.1186/s13063-021-05025-x
|View full text |Cite
|
Sign up to set email alerts
|

Mingjing granule, a traditional Chinese medicine in the treatment of neovascular age-related macular degeneration: study protocol for a randomized controlled trial

Abstract: Background Neovascular age-related macular degeneration (nAMD) is the most common cause of irreversible vision loss and blindness among the older people aged 50 and over. Although anti-vascular endothelial growth factor (anti-VEGF) therapies have resulted in improving patient outcomes, there are limitations associated with these treatments. In China, traditional Chinese medicine (TCM) has been used to treat eye diseases for more than 2000 years. Previous studies have shown that TCM may be benef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…e treatment is based on tonifying the liver and kidney, accompanied by removing the blood stasis and clearing collaterals, thus reducing the production of pathological VEGF [25][26][27][28][29]. Contemporary pharmacological studies show that part of traditional Chinese medicine for supplementing the liver and kidneys has antioxidation, stabilizes the blood-eye barrier, and has sex hormone-like effects [30][31][32][33][34]. In the clinical treatment of eye disease with the liver and kidney Yin syndrome, the use of Western medicine can be reduced to a certain extent by considering the combination of traditional Chinese and Western medicine.…”
Section: Discussionmentioning
confidence: 99%
“…e treatment is based on tonifying the liver and kidney, accompanied by removing the blood stasis and clearing collaterals, thus reducing the production of pathological VEGF [25][26][27][28][29]. Contemporary pharmacological studies show that part of traditional Chinese medicine for supplementing the liver and kidneys has antioxidation, stabilizes the blood-eye barrier, and has sex hormone-like effects [30][31][32][33][34]. In the clinical treatment of eye disease with the liver and kidney Yin syndrome, the use of Western medicine can be reduced to a certain extent by considering the combination of traditional Chinese and Western medicine.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been noted that compared with type 1 diabetes that T2D is not currently included in the fracture risk assessment tool (FRAX) used to calculate the 10-year fracture risk probability, which may be related to the fact that more than half of T2D patients are overweight or obese [ 17 ], and the impact of T2D on bone fragility is complex [ 18 ], with T2D patients generally having higher bone mineral density (BMD) than non-diabetic patients [ 19 ]. Patients with T2D often suffer from retinal macular degeneration, and one study reported that TCM Mingjing Granules can help to improve the safety and efficacy of intravitreal injections of anti–vascular endothelial growth factor in treating neovascular age-related macular degeneration [ 20 ]. This can further reduce the incidence of retinal macular degeneration in diabetic patients, a symptom which can lead to accidents such as falls and fractures due to poor vision.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of antioxidant nutrients reduced the risk for AMD (Raniga and Elder, 2009). Therefore, traditional Chinese herbs with antioxidant capacity are widely used in the clinical prevention of AMD (Jin et al, 2018;Li et al, 2021). Gastrodin, isolated from Gastrodia elata Blume, exerted antioxidant effect against retinal neurodegenerative diseases (Wang et al, 2017), high glucose-induced retinal endothelial cell apoptosis (Zhang et al, 2018), and glaucoma-related retinal degeneration (Molinari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%